The use of virtual reality in the stimulation of manual function in children with cerebral palsy: a systematic review - Kharinni Uchôa Pereira; Michelle Zampar Silva; Luzia Iara Pfeifer (Sociedade de Pediatria de São Paulo, 2023)
Abstract Objective: To identify in national and international literature the use of virtual reality to develop manual skills of children with cerebral palsy. Methods: This is a systematic review carried out in the PubMed database, Portal de Periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), and the Online System for Search and Analysis of Medical Literature (Ovid Medline) using the keywords "cerebral palsy", "virtual reality", "occupational therapy", "child", "daily activities/activities of daily living", in English and in Portuguese. The selected articles had their methodological quality evaluated through the Physiotherapy Evidence Database (PEDro scale). Results: 228 studies were selected, as they included children with cerebral palsy undergoing treatment with exposure to virtual reality to improve manual function in daily activities. Studies on other themes, incomplete, and duplicated reviews were excluded. Three evaluators conducted the study selection process and included 14 articles in the analysis. Conclusions: The findings suggest that virtual reality therapy has contributed to an improvement in the manual function of children with cerebral palsy, constituting a useful resource for a supporting intervention to enhance traditional therapies.